Embracing inclusiveness: A discourse analysis of cultural representation in Indonesian EFL textbook (Englisia : Journal of Language, Education, and Humanities, 2025)
In Indonesia, it is a national priority for students to develop the ability to interact and communicate with people from diverse backgrounds. Consequently, English as Foreign Language (EFL) textbooks play a crucial role in embedding this value. While previous studies have extensively explored multiculturalism in Indonesian EFL textbooks, little attention has been given to textbooks published internationally. This study addresses this gap by examining English in Mind Second Edition, an internationally published EFL textbook used by Indonesian junior high school students learning English. Employing a critical discourse analysis approach, this study investigates the inclusivity values portrayed in the textbook. The analysis reveals that the textbook demonstrates a strong commitment to promoting inclusivity. However, caution is advised when relying solely on this textbook to foster an inclusive educational environment in Indonesia. The use of foreign-published textbooks, while potentially controversial, offers a valuable opportunity to cultivate inclusivity.
Keywords: inclusiveness; multiculturalism; EFL; foreign language